Dissecting the Molecular and Cellular Mechanisms Underlying the Neurodegeneration - Ashok Chakraborty; Anil Diwan (Medical Research and Its Applications Vol. 7, 2024)
The present study focuses on Alzheimer’s disease (AD) and Parkinson’s disease (PD), since they vastly affect millions of people in the world, and occur when nerve cells lose functional ability and/or die over time. AD and PD, the likelihood of developing the issues rises dramatically with age. Degenerative nerve illnesses impact speech, breathing, mobility, balance, and heart function in the body. Neurodegenerative diseases can be categorized according to their molecular causes, such as aberrant protein aggregation, cell death, or loss of function of the implicated cell. Alzheimer’s disease (AD) is linked to tau, and amyloid-\(β\)42 protein accumulation, and Parkinson’s disease (PD) is connected with \(α\)-synuclein aggregation. The cause of disease may be genetic, and may also be sporadic. Alcoholism, pesticides, a tumor, or a stroke are sometimes noticed in the disease background. Sometimes the cause remains totally unknown. Neurodegeneration, to date, cannot be cured. Further, some types of NDD could also be fatal. Unfortunately, there is no cure at present for them except for some palliative measures to give some comfort to the victims. Increasing our knowledge of the cause(s) of neurodegenerative disorders may aid in the development of novel treatment and preventative strategies. These days, all neurodegenerative diseases can be better understood because of high-throughput technologies like RNA sequencing, network biology, and Omics data. Considering the importance of managing protein aggregates during aging and in neurodegenerative diseases, a detailed understanding of how those aggregates is formed and transferred. New research in the area of brain mechanisms may open a new avenue for disease prevention and treatment.